2020
DOI: 10.21037/qims-20-460
|View full text |Cite
|
Sign up to set email alerts
|

Combination of optical coherence tomography (OCT) and OCT angiography increases diagnostic efficacy of Parkinson’s disease

Abstract: Background: To assess the diagnostic efficacy of optical coherence tomography (OCT) and OCT angiography (OCTA) in Parkinson's disease (PD).Methods: OCT was used to obtain macular parameters and peripapillary retinal nerve fiber layer (RNFL) thickness. The macular superficial retinal vessel and foveal avascular zone (FAZ) were quantified with OCTA.The area under the receiver operating characteristic curve (AUC) indicated the diagnostic efficacy of the parameters.Results: Thirty-five eyes from 35 PD patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 42 publications
2
38
1
3
Order By: Relevance
“…Furthermore, we found that the decrease in FAZ area was accompanied by an increase in microvascular parameters in the foveal zone, like skeleton and perfusion density, fractal dimension or lacunarity. This contrasts with the results of Zou et al who found less vessel length and perfusion in the central macula of PD patients and no changes in FAZ area ( Zou et al, 2020 ), and with the results of Rascunà et al who did not find vascular density changes in the foveal zone of early PD patients ( Rascunà et al, 2020 ). Some of these differences might be attributed to smaller sample sizes, differences in disease stage of patients and study design flaws of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we found that the decrease in FAZ area was accompanied by an increase in microvascular parameters in the foveal zone, like skeleton and perfusion density, fractal dimension or lacunarity. This contrasts with the results of Zou et al who found less vessel length and perfusion in the central macula of PD patients and no changes in FAZ area ( Zou et al, 2020 ), and with the results of Rascunà et al who did not find vascular density changes in the foveal zone of early PD patients ( Rascunà et al, 2020 ). Some of these differences might be attributed to smaller sample sizes, differences in disease stage of patients and study design flaws of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In this work, we showed that foveal lacunarity could be a promising biomarker for differentiating patients from controls, as a significantly greater AUC was achieved after adding this parameter to the null model that controlled for confounding variables like age, sex, and hypertension. In a previous study of Zou et al (2020) , similar AUCs were obtained after combining OCT-A and OCT parameters. However, these authors only accounted for capillary length and density, and no further microvascular parameters were considered.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Optical coherence tomography angiography (OCTA) is a functional extension of optical coherence tomography (OCT) imaging that facilitates the visualization of microvascular and morphological structure non-invasively in the retina ( Spaide et al, 2018 ). Recently, several research findings described the decreased retinal microvascular density in patients with PD, which can serve as a surrogate biomarker for the diagnosis of PD ( Kwapong et al, 2018 ; Zou et al, 2020 ). However, studies focusing on whether altered retinal microvasculature affects visual function were scarce.…”
Section: Introductionmentioning
confidence: 99%
“…PD is related to the progressive loss of dopaminergic neurons as a consequence of α-synuclein accumulation within neuronal cytoplasm [ 7 ]. As a result, PD manifests with motor symptoms such as bradykinesia, resting tremor and rigidity [ 17 , 18 ]. Moreover, non-motor symptoms are also described, including sleep disorders, anosmia, depression, cognitive impairment and vision deficits [ 17 ].…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%